How do you simplify -4sqrt12 times 3 sqrt8 ?

2 Answers
Jun 19, 2016

-48sqrt(6)

Explanation:

you can write the equivalent expression:

-4sqrt(2^2*3)*3sqrt(2^2*2)

-4*2sqrt(3)*3*2sqrt(2)

-48sqrt(6)

Jun 19, 2016

To solve this family of problems you have to see if the numbers in the root can be factorized.

sqrt(12)=sqrt(4*3)=sqrt(4)*sqrt(3)=2sqrt(3)

in the same way sqrt(8)=2sqrt(2) (try it).

then we have:

-4sqrt(12)\times 3sqrt(8)

=-4*2*sqrt(3)\times3*2*sqrt(2)

=-8sqrt(3)\times6sqrt(2)

=-48sqrt(3)sqrt(2)

=-48sqrt(6).